PENGUKURAN KINERJA SISTEM INFORMASI PERPUSTAKAAN KABUPATEN SITUBONDO DENGAN PENDEKATAN IT BALANCED SCORECARD - Widiarti, Dian; Sandy, Rizka Gabriella; Damayanti, Deswita Putri; Putri, Hafisah Sucita; Yuliyanti, Kholifah (Relawan Jurnal Indonesia, 2024)
Situbondo Regency Library is one of the public service places that has a crucial role in providing access to the public to obtain information and literacy. As part of an effort to improve the quality of service, this library has implemented an information system to support its activities. This study aims to assess the effectiveness of the information system at the Situbondo Regency Library using the IT Balanced Scorecard (IT BSC) approach. IT BSC is a method that evaluates information technology performance from four main perspectives, namely contribution to business, user focus, operational capability, and future vision. This approach provides a comprehensive perspective on information system performance by considering strategic and operational aspects. The methods applied include a combination of quantitative data collection through surveys of system users and qualitative analysis through interviews with library management. The results of the study indicate that the contribution of the information system to achieving library business targets is good based on the final achievement score of 74.46%. The highest score is in the company contribution perspective of 24.51%, then the future orientation perspective of 23.87%, followed by the user orientation perspective of 16.64% and finally the operational excellence perspective of 9.44%. Thus, this study presents a comprehensive picture of the performance of information systems at the Situbondo Regency Library while providing strategic input for the development of information technology in the future.